1995
DOI: 10.1007/bf00127976
|View full text |Cite
|
Sign up to set email alerts
|

A new system for the expression of recombinant antibody in mammalian cells

Abstract: New type of plasmids named pEdHCG1 and pEdHC~:.were constructed. A combination of two plasmids containing the amplified gene product for the variable region of the antibody (Ab) heavy or light chains by the polymerase chain reaction (PCR) was co-transfected into COS cells to transiently express and in Chinese hamster ovary (CHO) cells to constitutively express chimeric Ab composed of the mouse-derived variable region and human-derived constant region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Some efforts have been paid in order to overcome the difficulty in application of IgM. Screening class switch variants producing IgG mAbs from IgM-producing cells (Steplewski et al, 1985) and preparing single-chain antibodies by gene engineering (Winter and Milstein, 1991;Iba et al, 1995) are the examples. We have recently developed a convenient method for the preparation of F(ab') 2 fragments of 145 kDa from pepsin digests of mouse and rat IgM mAbs (Inouye and Morimoto, 1993a, 1993b, 1994 and suggested that the term F(ab') 2 should be used instead of F(ab') 2 to indicate that the fragments are prepared from IgM by cleaving the heavy chains.…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been paid in order to overcome the difficulty in application of IgM. Screening class switch variants producing IgG mAbs from IgM-producing cells (Steplewski et al, 1985) and preparing single-chain antibodies by gene engineering (Winter and Milstein, 1991;Iba et al, 1995) are the examples. We have recently developed a convenient method for the preparation of F(ab') 2 fragments of 145 kDa from pepsin digests of mouse and rat IgM mAbs (Inouye and Morimoto, 1993a, 1993b, 1994 and suggested that the term F(ab') 2 should be used instead of F(ab') 2 to indicate that the fragments are prepared from IgM by cleaving the heavy chains.…”
Section: Introductionmentioning
confidence: 99%